MEDICAL, SOCIAL AND CLINICAL ASPECTS OF DYSCIRCULATORY ENCEPHALOPATHY IN PATIENTS OF WORKING AGE - Litvin, O.V.; Kondratiuk, N.Yu.; Gandzyuk, V.А. (World of Medicine and Biology, 2019)
The increase in the number of cerebrovascular diseases (CVD) in our country is mainly due to the chronic, slowly progressing forms - dyscirculatory encephalopathies. According to world statistics, the main cause of neurological disability is stroke. Among patients with CVD, more than 15%, given the pronounced permanent functional disorders, are treated in nursing facilities. Most of the patients suffering from stroke have this or that kind of disability after 7 years. This situation leads to an increase in the demographic burden on the working-age population. The purpose of the work was to study the medical, social and clinical aspects of the dyscirculatory encephalopathy course in people of working age. According to the results of the study, it was proved that in patients with dyscirculatory encephalopathy (DE) and arterial hypertension (AH) there was a significant increase in vascular elasticity, but atherosclerotic vascular damage was higher in patients with DE. A feature of cerebrovascular events in government employees with hypertensive dyscirculatory encephalopathy is an increase in vascular resistance in the internal carotid and medial cerebral arteries.
Keywords: dyscirculatory encephalopathy; arterial hypertension; cognitive impairment; medical and social aspect